Coastal erosion: from coastal natural resources loss to territorial imbalances and social impacts - Duarte de Almeida, I. (2021)
This mini-review addresses the Coastal erosion dilemma with which governments seek to deal. The problem stems from coastal attractiveness to society since coastal regions are rich in biodiversity, provide food, transportation, and recreation, appealing to people and economic activities. Consequently, they are becoming densely populated areas which is determinant to the coastal erosion escalation. The growth and diversity of activities located in coastal regions that directly or indirectly depend on them have led to increasing pressures with damaging ecosystems and accelerating coastal erosion. Damming, dredging, inert extraction, fluvial and marine engineering works, and coastal zones' urbanisation have all caused profound imbalances in the natural systems. Among other things, these imbalances have reduced the amount of sediments arriving at the littoral, contributing to coastal ecosystems' degradation and diminishing their resilience in extreme weather events. On the other hand, if some of those pressures result from societies' development and highly urbanised coastal areas, others are directly related to natural processes potentiated by global warming. In any of these situations, the path drawn is that of leading to degradation and over-utilisation, jeopardising coastal natural resources. This paper aims to present some results and details of an ongoing research project on the social-economic and environmental impact of coastal erosion in a Portuguese coastal urban area.